Theory of Mind in Offending: A Systematic Review. (December 2022) - Karoğlu, Nilda; Ferguson, Heather J.; Ó Ciardha, Caoilte
Theory of mind (ToM) impairment is associated with poor social functioning in some psychological disorders (e.g., autism and schizophrenia). ToM deficits have also been linked with offending behavior in the theoretical literature. However, no review has examined the empirical evidence for such a link. We carried out a systematic review to provide a critical overview of studies involving ToM ability in offenders. We included studies published in English that used an instrument to measure at least one aspect of ToM. Twenty-eight eligible studies were identified and coded. Our findings reveal a generally mixed literature. Taking study quality into account, our findings suggest that offenders and nonoffenders do not differ in their first-order ToM. For second-order ToM, findings are mixed, even when only the highest quality studies are examined. Studies exploring advanced ToM showed mixed results overall, though the highest quality research appeared to indicate that offenders have impairments in advanced ToM which means that they may have difficulty understanding various mental states such as pretense, white lies, irony, double bluffs, and sarcasm. We suggest that well-controlled future studies, which also measure other facets of ToM (e.g., distinguishing between cognitive and affective ToM or examining ToM content), are needed to fully understand the role of ToM in offending.